Ação de formigas do gênero Atta (Hymenoptera: formicidae) na composição, distribuição e preservação da assembleia de fitólitos de um latossolo: um estudo em micro e macro escala - Benincá, Carolina Glaeser (2024)
The investigation of phytolith assemblages of soils and sediments is widely recognized as an abundant source of reliable information about past vegetation, being extensively applied in paleoenvironmental studies worldwide. Phytoliths are plant microfossils made of hydrated silica that are frequently preserved in soils and sediments. Their durability, abundance, and diagnostic morphologies make them reliable environmental proxies, especially when combined with other biological, physical, and/or chemical markers. The preservation, conservation, and distribution of phytoliths in soil are conditioned by numerous environmental factors and processes that can impact the taphonomy of these cells, causing disturbances in their natural distribution and morphology. Understanding the context in which phytoliths are deposited is essential to avoid superficial or erroneous paleoenvironmental interpretations, as they are subject to degradation and movement due to surface runoff over short distances, lateral and vertical movement within the soil due to soil-plant-solute interactions, soil hydrological processes, and bioturbation. The physical effects of soil fauna include mixing, stacking, and burying of soil, they also affect the soil's chemical balance transporting animal and plant remains to deeper soil layers where they decompose. Additionally, they affect the physical structure of the soil through the construction of mounds, galleries, and nests, altering porosity patterns and the formation and destruction of soil aggregates. Although recognized, the impact of bioturbation and its relationship with the distribution and conservation of biogenic silica in the soil profile is still poorly understood, especially in tropical regions where biological activity in soils is high. In this context, this dissertation aims to contribute to the understanding of the effects of bioturbation promoted by leafcutter ants (Atta Hymenoptera: Formicidae) colonies on the soil’s phytolith assemblage by identifying and describing the effects of these insects on the distribution and preservation of phytolith assemblages and their possible impacts on paleoenvironmental interpretations. The study area selected is in western Paraná, a region with a predominance of Oxisols, whose genesis is closely related to biological activity and high weathering rates. Two nearby profiles were chosen, one for reference and the other under the activity of leafcutter ant’ colony. The results show that in the studied area, the impacts of ant activity did not significantly alter the natural (reference) pattern of phytolith distribution and preservation to the point of significantly interfering in paleoenvironmental interpretations. However, it is noticeable that leafcutter ants transport mineral material vertically within the profile, in addition to promoting the input of fresh plant tissues and the output of residual materials, all potentially containing varied phytolith assemblages. Additionally, higher values and a more irregular distribution pattern were observed in the number of taphonomized phytoliths of the profile under the ant’s colony compared to the reference profile, as well as alterations in the linearity of isotopic data in depth.